Excess body weight and four‐year function outcomes: Comparison of African Americans and whites in a prospective study of osteoarthritis1. Issue 1 (27th December 2012) - Colbert, Carmelita J.; Almagor, Orit; Chmiel, Joan S.; Song, Jing; Dunlop, Dorothy; Hayes, Karen W.; Sharma, Leena
Abstract Objective We evaluated whether African Americans in the Osteoarthritis Initiative (OAI) have a greater risk (versus whites) of poor 4‐year function outcome within strata defined by sex, body mass index (BMI), and waist circumference. Methods Using Western Ontario and McMaster Universities Osteoarthritis Index function, 20‐meter walk, and chair stand performance, poor outcome was defined as moving into a worse function group or remaining in the 2 worst groups over 4 years. Logistic regression was used to evaluate the relationship between racial group and outcome within each stratum, adjusting for age, education, and income, and then further adjusting for BMI, comorbidity, depressive symptoms, physical activity, knee pain, and osteoarthritis (OA) severity. Results In 3, 695 persons with or at higher risk for knee OA, higher BMI and large waist circumference were each associated with poor outcome. Among women with high BMI and among women with large waist circumference, African Americans were at greater risk for poor outcome by every measure, adjusting for age, education, and income. From fully adjusted models, potential explanatory factors included income, comorbidity, depressive symptoms, pain, and disease severity. Findings were less consistent for men, emerging only for the 20‐meter walk or chair stand outcomes, and potentially explained by age and knee pain. Conclusion Among OAI women with excess body weight, African Americans are at greater risk than whites for poor 4‐year outcome. Modifiable factors that may help to explain these findings in the OAI include comorbidity, depressive symptoms, and knee pain. Targeting such factors, while supporting weight loss, may help to lessen the outcome disparity between African American and white women.